SPEECH ACT IN CODE MIXING IN A.R. RIZAL'S NOVEL LIMPAPEH - Afrinda, Putri Dian; Delpa, Delpa; Asmul, Ali; Fitriyah, Rifkah; Mustika, Nova (ppjbsip, 2021)
This study discusses the author's speech acts and how they were utilised in his work. In the novel Limpapeh by Ar. Rizal, this study will describe speech acts in the form of code mixing that create code mixing, forms of code mixing, and the function of code mixing. In addition to showing cultural identity, the code mixing used by the author can also serve as an affirmation or explain something, showing familiarity with certain calls as a form of respect for others. Thus, the author deliberately inserts the term area of origin as part of his identity. Readers can recognize the culture of an area, especially Minangkabau from the works they produce. This research will describe the factors that cause code mixing, code mixing functions, and types of code mixing in the speech of the Limpapeh novel characters. The method used in this study is a reflective-introspective analysis method. It is possible that the phenomenon of using language is lived in everyday life. Provision of data in this study in the form of written text. The code mixing that occurs is conveyed by the author through the naming of cooking spices, dishes, people's names and proverbs or terms commonly used in the Minangkabau community. In AR RIZAL's novel Limpapeh, the type of speech act used in Minangkabau society is forceful speech with the style of asserting.